Pembuatan Cetakan Kotak Sabun Pada Mesin Injection Molding Plastik - Rakhmad Arief Siregar; Ahmad Ridwan Rangkuti (Rekayasa Material, Manufaktur dan Energi, 2018)
Products made from plastic at this time we often encounter human life in various forms, so that there are many product requests or tools made of plastic make mold orders mold making is increasing. In the process of forming plastic with the injection molding method need to be made a mold, mold is the most important part for printing plastic because the shape of a plastic object depends from the shape of the mold. In particular Al-7075 alloy with a composition of 5.5% Zn, 2.5-1.5% Mn, 1.5% Cu, 0.3% Cr, 0.2% Mn. The size of the soapbox mold after milling is: length of 140 mm and width of 105 mm, for the cavity or the so-called female has a thickness of 31 mm while the core which is referred to as male is 41 mm thick. Process carried out in making this mold using a milling machine by working on the adjustment process, radius screening, straight, drillingand finishing hexagons. The injection molding process uses a heater (heater) that has been made in the form of a tube and then filled with plastic and plastic is thawed in a heating tube with a temperature of 250 ℃ and the liquid plastic liquid was pressed so that it exits the nozzle and goes into the mold (liquid) plastic that has been moved into the mold then cooled until hardened until a soap box product is formed.